In-situ construction of MOF / LDH / PDA / PVDF composite membrane material for separating oil-water emulsion, preparation method and application

CN122974151APending Publication Date: 2026-10-27CHENGDU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611292120.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]为解决现有技术中油水分离膜材料制备工艺复杂、成本较高或分离通量不足等问题,本发明提出了一种油水乳液分离用的原位构筑MOF/LDH/PDA/PVDF复合膜材料、制备方法和应用

Benefits of technology

本发明所提供的MOF/LDH/PDA/PVDF复合膜材料,原料易得,制备工艺温和可控,操作简便。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974151A_ABST
    Figure CN122974151A_ABST
Patent Text Reader

Abstract

The application discloses an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation, a preparation method and application, and belongs to the field of environmental functional materials and water treatment technologies.The membrane material is obtained by sequentially performing alkali treatment, dopamine modification, in-situ growth of cobalt-iron layered double hydroxide and cobalt-based metal organic framework loading treatment on a hydrophobic polyvinylidene fluoride membrane.The membrane material has hydrophilicity and underwater superoleophobicity, is suitable for rapid separation of oil-water mixtures and oil-water emulsions, and has the advantages of large separation flux, strong anti-fouling capacity, good cycle stability and the like.The application adopts a mild and controllable layer-by-layer self-assembly synthesis method, raw materials are low in price, the preparation process is simple, operation is convenient, the period is short, and the application is easy to scale up, and therefore, has good application value and market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmental functional materials and water treatment technology, and particularly relates to an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation, its preparation method and application. Background Technology

[0002] With the large-scale discharge of oily wastewater from industry and the frequent occurrence of marine oil spills, oil-water separation has become one of the most pressing environmental problems to be solved globally. Traditional oil-water separation methods mainly include gravity sedimentation, flotation, centrifugation, and adsorption, but these methods generally suffer from drawbacks such as low separation efficiency, high energy consumption, and the potential for secondary pollution. Membrane separation technology, due to its advantages of high separation efficiency, simple operation, and relatively low energy consumption, shows promising application prospects in the field of oil-water separation.

[0003] Currently, various superhydrophilic / submarine superoleophobic membrane materials have been reported for oil-water separation, such as metal oxide membranes and hydrogel-coated membranes. However, existing membrane materials still have the following shortcomings: on the one hand, some preparation methods involve complex synthesis steps or require harsh reaction conditions, resulting in high production costs and hindering large-scale production; on the other hand, most membrane materials are easily contaminated by oil during long-term use, causing a decrease in separation flux and efficiency, and are difficult to clean and regenerate, resulting in poor recyclability.

[0004] Polyvinylidene fluoride (PVDF) membranes are widely used as separation membrane substrates due to their excellent mechanical properties and chemical stability. However, the hydrophobicity of PVDF membranes makes them susceptible to oil fouling, thus limiting their application in oily wastewater treatment. Surface hydrophilic modification is an effective strategy to improve the antifouling performance of PVDF membranes. Existing technologies often employ surface coating or grafting of hydrophilic polymers, or the introduction of inorganic nanoparticles for modification, but problems such as poor coating stability and uneven modified layers still exist. Furthermore, layered bimetallic hydroxides (LDHs) and metal-organic frameworks (MOFs) have attracted attention in the field of membrane separation due to their unique structures and surface properties. However, how to achieve a simple and stable composite of LDHs and MOFs with PVDF membranes, and endow the composite membrane material with excellent underwater superoleophobic properties and self-cleaning capabilities, remains a pressing technical problem to be solved in this field.

[0005] In existing research, modified membranes using polydopamine-anchored and in-situ grown layered bimetallic hydroxide (LDH) and modified membranes loaded with metal-organic frameworks (MOFs) have been used for oil-water separation. However, there are no reports on constructing composite membrane materials with both micro- and nano-rough structures by progressively compositing the in-situ grown LDH bottom layer and the in-situ grown MOF top layer onto the same polyvinylidene fluoride membrane. How to further improve the underwater superoleophobicity, oil resistance, and separation flux of the membrane through this progressive in-situ construction strategy is the technical problem this invention aims to solve. Summary of the Invention

[0006] To address the problems of complex preparation processes, high costs, or insufficient separation flux in existing oil-water separation membrane materials, this invention proposes an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation, its preparation method, and its application.

[0007] To achieve the above objectives, the present invention provides the following technical solution: An in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation is composed of a polymer base membrane and a polydopamine layer, a layered bimetallic hydroxide layer and a metal-organic framework layer sequentially constructed in situ on its surface. The polymer base membrane is a hydrophilic polyvinylidene fluoride membrane; The layered bimetallic hydroxide is a cobalt-iron layered bimetallic hydroxide; The metal-organic framework is formed by cobalt ions coordinated with 2,3,6,7,10,11-hexahydroxytriphenyl ligands.

[0008] This invention employs an in-situ growth construction method. First, a hydrophobic polyvinylidene fluoride (PVDF) membrane is alkali-treated to convert it to hydrophilicity. Then, a polydopamine layer is formed on the hydrophilic PVDF membrane. Next, a layered bimetallic hydroxide (BHH) layer is grown in situ on the surface of the BHH layer. Finally, a metal-organic framework (MOF) layer is grown in situ on the surface of the BHH layer, resulting in a MOF / LDH / PDA / PVDF composite membrane. This invention obtains a composite membrane material by sequentially subjecting a hydrophobic PVDF membrane to alkali treatment, dopamine modification, in-situ growth of cobalt-iron layered BHH, and loading a cobalt-based MOF onto the membrane. This membrane material exhibits hydrophilicity and underwater superoleophobic properties, making it suitable for the rapid separation of oil-water mixtures and oil-water emulsions. It offers advantages such as high separation flux, strong antifouling ability, and good cycle stability. This invention utilizes a mild and controllable layer-by-layer self-assembly synthesis method, using inexpensive raw materials. The preparation process is simple, convenient, and has a short cycle time, demonstrating good application value and market prospects.

[0009] Furthermore, the polydopamine layer is formed by the self-polymerization of dopamine under alkaline conditions.

[0010] Furthermore, the hydrophilic polyvinylidene fluoride membrane is obtained by treating a hydrophobic polyvinylidene fluoride membrane with an alkali.

[0011] This invention also provides a method for preparing an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation, comprising the following steps: (1) The hydrophobic polyvinylidene fluoride membrane was placed in an alkaline solution and reacted under heating conditions. After the reaction was completed, it was washed and dried to obtain a hydrophilic polyvinylidene fluoride membrane. (2) The hydrophilic polyvinylidene fluoride membrane obtained in step (1) is immersed in Tris-HCl buffer containing dopamine and stirred continuously at room temperature. After the reaction is completed, it is washed and dried to obtain a PDA / PVDF membrane. (3) Prepare organic solvent solutions of cobalt salt and aqueous solutions of ferrous salt respectively. After mixing the two solutions, immerse the PDA / PVDF membrane obtained in step (2) into it and stir the reaction at room temperature. After the reaction is completed, wash and dry to obtain LDH / PDA / PVDF membrane. (4) Immerse the LDH / PDA / PVDF membrane obtained in step (3) in a cobalt salt aqueous solution and let it stand. Then add an organic solvent solution containing 2,3,6,7,10,11-hexahydroxytriphenyl ligands and let it stand at room temperature for reaction. After the reaction is completed, wash and dry to obtain the MOF / LDH / PDA / PVDF composite membrane.

[0012] Further, the alkaline solution mentioned in step (1) is a 0.8-1.2M sodium hydroxide solution containing 3-7 wt% ethanol; The reaction temperature under the heating conditions is 50~70℃, and the reaction time is 1~3 hours.

[0013] Furthermore, the concentration of dopamine in step (2) is 1.5~2.5 mg / mL; The concentration of the Tris-HCl buffer solution is 0.08~0.12M, and the pH value is 8.0~9.0; The continuous stirring reaction lasts for 4 to 8 hours.

[0014] Further, the cobalt salt mentioned in step (3) is at least one of cobalt nitrate, cobalt chloride, and cobalt acetate; The ferrous salt is at least one of ferrous sulfate, ferrous chloride and ferrous nitrate; The organic solvent is at least one of isopropanol, ethanol, and methanol; The volume ratio of the organic solvent solution of the cobalt salt to the aqueous solution of the ferrous salt is 2:1 to 4:1, and the concentration of the metal salt in both solutions is 0.1 to 0.3 M. The stirring reaction at room temperature is carried out for 20 to 28 hours.

[0015] Further, the cobalt salt mentioned in step (4) is at least one of cobalt nitrate, cobalt chloride and cobalt acetate, and the concentration of the cobalt salt in its aqueous solution is 1~3 mg / mL; In the organic solvent solution containing 2,3,6,7,10,11-hexahydroxytriphenyl ligands, the solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide and ethylene glycol, and the concentration of the ligand is 20~30 mg / mL; The volume ratio of the cobalt salt aqueous solution to the ligand-containing organic solvent solution is 8:1 to 10:1; The settling time is 0.5 to 2 hours; The time for the reaction to stand at room temperature is 20 to 28 hours.

[0016] This invention also provides an application of an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation.

[0017] Furthermore, the oil-water separation is oil-water mixture separation and / or oil-water emulsion separation; The oil in the oil-water mixture separation is selected from at least one of the following: toluene, dichloroethane, petroleum ether, n-octane, and diesel oil; The oil-water emulsion separation refers to the separation of oil-water emulsions without surfactants or oil-water emulsions containing surfactants.

[0018] Compared with the prior art, the present invention has the following advantages and technical effects: The MOF / LDH / PDA / PVDF composite membrane material provided by this invention uses readily available raw materials, has a mild and controllable preparation process, and is easy to operate.

[0019] The composite membrane material provided by this invention has advantages such as fast separation speed and good separation effect. It is suitable for the separation and treatment of oil-water mixtures and oil-in-water emulsions. It can effectively separate oil-water mixtures and oil-in-water emulsions containing oils such as dichloroethane, petroleum ether, toluene, diesel oil and n-octane.

[0020] The composite membrane material provided by this invention has excellent underwater superoleophobic properties (contact angle >150°), strong antifouling ability, good stability, and can be recycled.

[0021] Furthermore, this invention constructs a two-level micro / nano roughness structure by sequentially growing cobalt-iron layered bimetallic hydroxide nanosheets and cobalt-based metal-organic framework particles in situ on a polydopamine layer. The layered bimetallic hydroxide provides abundant hydrophilic groups and primary nanosheet roughness, while the metal-organic framework particles further provide a porous structure and secondary roughness. The two work synergistically to enhance the hydration layer and underwater superoleophobicity of the membrane surface, reducing oil droplet adhesion, improving antifouling and cycle stability, while also achieving a high separation flux. To the applicant's knowledge, this invention is the first to use a metal-organic framework formed by the coordination of cobalt ions with 2,3,6,7,10,11-hexahydroxytriphenyl ligands in an oil-water separation membrane. Attached Figure Description

[0022] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 A digital photograph of the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation prepared in Example 1; Figure 2 The image shows a scanning electron microscope (SEM) image of the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation prepared in Example 1. Figure 3 Atomic force microscopy (AFM) image of the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation prepared in Example 1; Figure 4 The above are X-ray photoelectron spectra (XPS) of the PVDF film, LDH / PDA / PVDF film, and MOF / LDH / PDA / PVDF film in Example 1. Figure 5 To measure in water the contact angle of (a) the surface of the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation prepared in Example 1 with dichloroethane, petroleum ether, toluene, diesel oil and n-octane; and (b) the roll-off angle of the surface of the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation prepared in Example 1 with dichloroethane; Figure 6 The diagram shows the experimental setup for separating oil-water mixtures and oil-water emulsions using the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material prepared in Example 1. Figure 7The separation flux and separation efficiency of the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation prepared in Example 1 for five kinds of oil-water emulsions (a) and the circulating separation test of petroleum ether / water mixed emulsion (b) are shown. Figure 8 The images show the effect of the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation prepared in Example 1 on oil-water emulsion separation; where (a) is an optical microscope photograph of the oil-water emulsion; (b) is a digital photograph of the oil-water emulsion and the filtrate; and (c) is an optical microscope photograph of the filtrate. Detailed Implementation

[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0024] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0025] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0026] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This specification and embodiments are merely exemplary.

[0027] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0028] This invention provides a method for preparing an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation, comprising the following steps: (1) Place the hydrophobic polyvinylidene fluoride membrane in a 0.8-1.2M sodium hydroxide solution containing 3-7wt% (e.g., 3wt% or 5wt%) ethanol and react it at 50-70℃ (e.g., 50℃, 60℃, 65℃ or 70℃) for 1-3 hours (e.g., 1 hour, 2 hours or 3 hours). After the reaction is completed, wash and dry at 40-60℃ (e.g., 40℃, 50℃ or 60℃) to obtain a hydrophilic polyvinylidene fluoride membrane. (2) Immerse the hydrophilic polyvinylidene fluoride membrane obtained in step (1) in a Tris-HCl buffer containing 1.5~2.5 mg / mL (e.g., 1.5 mg / mL, 2.0 mg / mL or 2.5 mg / mL) of dopamine, wherein the buffer concentration is 0.08~0.12 M (e.g., 0.08 M, 0.1 M or 0.12 M) and the pH value is 8.0~9.0 (e.g., 8.0, 8.5 or 9.0), and stir continuously at room temperature for 4~8 hours (e.g., 4 hours, 6 hours, 7 hours or 8 hours). After the reaction is completed, wash and dry at 40~60℃ (e.g., 40℃, 50℃ or 60℃) to obtain a PDA / PVDF membrane; (3) Prepare 0.1~0.3M (e.g. 0.15M, 0.2M or 0.25M) cobalt salt (e.g. cobalt nitrate, cobalt chloride or cobalt acetate) in an organic solvent (e.g. isopropanol, ethanol or methanol) and an aqueous solution of ferrous salt (e.g. ferrous sulfate, ferrous chloride or ferrous nitrate). Mix the two solutions in a volume ratio of 2:1~4:1 (e.g. 2:1, 3:1 or 4:1). Immerse the PDA / PVDF membrane obtained in step (2) in the mixture and stir at room temperature for 20~28 hours (e.g. 20 hours, 24 hours, 26 hours or 28 hours). After the reaction is completed, wash and dry at 40~60℃ (e.g. 40℃, 50℃ or 60℃) to obtain the LDH / PDA / PVDF membrane. (4) Immerse the LDH / PDA / PVDF membrane obtained in step (3) in an aqueous solution of 1~3 mg / mL (e.g., 1 mg / mL, 2 mg / mL or 3 mg / mL) of cobalt salt (e.g., cobalt nitrate, cobalt chloride or cobalt acetate) and let it stand for 0.5~2 hours (e.g., 0.5 hours, 1 hour, 1.5 hours or 2 hours). Add 2,3,6,7,10,11-hexahydroxytriphenyl ligand containing 20~30 mg / mL (e.g., 20 mg / mL, 25 mg / mL or 30 mg / mL). An organic solvent solution (such as N,N-dimethylformamide, N,N-dimethylacetamide, or ethylene glycol) is used, and the volume ratio of the cobalt salt aqueous solution to the ligand-containing organic solvent solution is 8:1 to 10:1 (e.g., 8:1, 9:1, or 10:1). The reaction is allowed to stand at room temperature for 20 to 28 hours (e.g., 20 hours, 24 hours, 26 hours, or 28 hours). After the reaction is completed, the membrane is washed and dried at 40 to 60°C (e.g., 40°C, 50°C, or 60°C) to obtain the MOF / LDH / PDA / PVDF composite membrane.

[0029] Using the above preparation method, an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation can be prepared, and this material can be applied in oil-water separation. Oil-water separation includes the separation of oil-water mixtures and / or oil-water emulsions; the oil in the oil-water mixture separation is selected from at least one of the following: toluene, dichloroethane, petroleum ether, n-octane, and diesel oil; oil-water emulsion separation includes the separation of oil-water emulsions without surfactants or oil-water emulsions containing surfactants.

[0030] When separating oil-water mixtures, the membrane material can be moistened with water first, and then the oil-water mixture can be passed through the membrane material. The water passes through the membrane material while the oil is retained, thereby achieving the purpose of oil-water separation.

[0031] Oil-water emulsions without surfactants, such as oil-in-water emulsions; oil-water emulsions containing surfactants, such as emulsions containing sodium dodecyl sulfate and / or Tween 80.

[0032] When the oil-water emulsion is an oil-in-water emulsion, the emulsion is passed through the membrane material, the emulsion is broken, the water passes through the membrane material while the oil is retained.

[0033] The in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation provided by this invention has the properties of being superhydrophilic and superoleophilic in air (with contact angles with water and oil close to 0° in air), superoleophobic underwater (with contact angles with oil droplets greater than 150° underwater), and superhydrophobic under oil (with contact angles with water droplets greater than 150° under oil). Specifically, it can be used for oil-water separation of oily wastewater (such as that containing dichloroethane, petroleum ether, toluene, diesel, and n-octane) and separation of oil-in-water emulsions.

[0034] Unless otherwise specified, "room temperature" in this invention refers to 25±2℃.

[0035] All raw materials used in this invention were purchased from the market.

[0036] Without any theoretical limitations, the in-situ generation mechanism of the layered bimetallic hydroxide in step (3) of this invention can be understood as follows: the polydopamine layer is rich in active groups such as catechol and amino groups, which provide abundant anchoring and nucleation sites for metal cations and create a slightly alkaline local microenvironment; in the open oxygen-containing system, the ferrous ions provided by the ferrous salt can be partially oxidized in situ to ferric ions, and then co-deposited with cobalt ions on the film surface and grown in situ into cobalt-iron layered bimetallic hydroxide nanosheets.

[0037] Similarly, in step (4), 2,3,6,7,10,11-hexahydroxytriphenyl is a catechol-type ligand, which coordinates with cobalt ions after aerobic oxidation in an open oxygen-containing system, and grows in situ on the surface of layered bimetallic hydroxide nanosheets to form a metal-organic framework particle layer; the reaction process does not require the isolation of air.

[0038] The technical solution of the present invention will be further illustrated by the following embodiments.

[0039] Example 1 A method for preparing an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation includes the following steps: (1) The hydrophobic polyvinylidene fluoride membrane was placed in a 1.0M sodium hydroxide solution containing 5wt% ethanol and reacted at 60°C for 2 hours. After the reaction was completed, it was rinsed and dried at 50°C to obtain a hydrophilic polyvinylidene fluoride membrane. (2) The hydrophilic polyvinylidene fluoride membrane obtained in step (1) was immersed in Tris-HCl buffer containing dopamine, wherein the concentration of dopamine was 2.0 mg / mL, the concentration of Tris-HCl buffer was 0.1 M, the pH value was 8.5, and the reaction was stirred continuously at room temperature for 6 hours. After the reaction was completed, the membrane was rinsed and dried at 50°C to obtain the PDA / PVDF membrane. (3) Prepare isopropanol solution of cobalt nitrate and aqueous solution of ferrous sulfate respectively. The concentration of metal salt in both solutions is 0.2M. After mixing them at a volume ratio of 3:1, immerse the PDA / PVDF membrane obtained in step (2) into it, stir at room temperature for 24 hours, rinse after the reaction is completed, and dry at 50°C to obtain LDH / PDA / PVDF membrane. (4) The LDH / PDA / PVDF membrane obtained in step (3) was immersed in a cobalt acetate aqueous solution and allowed to stand for 1 hour. The concentration of cobalt acetate was 2.0 mg / mL. Then, an N,N-dimethylformamide solution containing 25 mg / mL of 2,3,6,7,10,11-hexahydroxytriphenyl ligand was added. The volume ratio of the cobalt acetate aqueous solution to the N,N-dimethylformamide solution containing 25 mg / mL of 2,3,6,7,10,11-hexahydroxytriphenyl ligand was 9:1. The membrane was allowed to stand at room temperature for 24 hours. After the reaction was completed, the membrane was rinsed and dried at 50°C to obtain the MOF / LDH / PDA / PVDF composite membrane.

[0040] Figure 1 A digital photograph of the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation prepared in Example 1; Figure 2 This is a scanning electron microscope image of the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation prepared in Example 1; Figure 2 As can be seen, MOF particles are uniformly distributed along the three-dimensional network framework of the PVDF film, forming a complete coating layer.

[0041] Figure 3 This is an atomic force microscope image of the in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation prepared in Example 1; Figure 3 It can be seen that the surface arithmetic mean roughness (Ra) of the composite membrane is 406 nm, which is beneficial to improving the hydrophilicity and oil-water separation performance of the membrane.

[0042] Figure 4 The X-ray photoelectron spectra of the PVDF film, LDH / PDA / PVDF film, and MOF / LDH / PDA / PVDF film in Example 1 are shown. The characteristic peaks of elements such as C, N, O, Co, and Fe appeared in the full XPS spectrum, confirming the successful construction of the MOF / LDH / PDA / PVDF composite film.

[0043] Example 2 A method for preparing an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation includes the following steps: (1) The hydrophobic polyvinylidene fluoride membrane was placed in a 0.8M sodium hydroxide solution containing 3wt% ethanol and reacted at 50°C for 3 hours. After the reaction was completed, it was rinsed and dried at 40°C to obtain a hydrophilic polyvinylidene fluoride membrane. (2) The hydrophilic polyvinylidene fluoride membrane obtained in step (1) was immersed in Tris-HCl buffer containing dopamine, wherein the concentration of dopamine was 1.5 mg / mL, the concentration of Tris-HCl buffer was 0.08 M, the pH value was 8.0, and the reaction was stirred continuously at room temperature for 4 hours. After the reaction was completed, the membrane was rinsed and dried at 40°C to obtain the PDA / PVDF membrane. (3) Prepare an ethanol solution of cobalt chloride and an aqueous solution of ferrous chloride respectively. The concentration of metal salt in both solutions is 0.15M. After mixing them at a volume ratio of 2:1, immerse the PDA / PVDF membrane obtained in step (2) into it, stir at room temperature for 20 hours, rinse after the reaction is completed, and dry at 40°C to obtain an LDH / PDA / PVDF membrane. (4) The LDH / PDA / PVDF membrane obtained in step (3) was immersed in a cobalt nitrate aqueous solution and allowed to stand for 0.5 hours. The cobalt nitrate concentration was 1.0 mg / mL. Then, an N,N-dimethylformamide solution containing 20 mg / mL of 2,3,6,7,10,11-hexahydroxytriphenyl ligand was added. The volume ratio of the cobalt nitrate aqueous solution to the N,N-dimethylformamide solution containing 20 mg / mL of 2,3,6,7,10,11-hexahydroxytriphenyl ligand was 8:1. The membrane was allowed to stand at room temperature for 20 hours. After the reaction was completed, the membrane was rinsed and dried at 40°C to obtain the MOF / LDH / PDA / PVDF composite membrane.

[0044] Example 3 A method for preparing an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation includes the following steps: (1) The hydrophobic polyvinylidene fluoride membrane was placed in a 1.2M sodium hydroxide solution containing 7wt% ethanol and reacted at 70°C for 1 hour. After the reaction was completed, it was rinsed and dried at 60°C to obtain a hydrophilic polyvinylidene fluoride membrane. (2) The hydrophilic polyvinylidene fluoride membrane obtained in step (1) was immersed in Tris-HCl buffer containing dopamine, wherein the concentration of dopamine was 2.5 mg / mL, the concentration of Tris-HCl buffer was 0.12 M, the pH value was 9.0, and the reaction was stirred continuously at room temperature for 8 hours. After the reaction was completed, the membrane was rinsed and dried at 60°C to obtain the PDA / PVDF membrane. (3) Prepare a methanol solution of cobalt acetate and an aqueous solution of ferrous nitrate respectively. The concentration of metal salt in both solutions is 0.25M. After mixing them at a volume ratio of 4:1, immerse the PDA / PVDF membrane obtained in step (2) into it, stir at room temperature for 28 hours, rinse after the reaction is completed, and dry at 60°C to obtain an LDH / PDA / PVDF membrane. (4) The LDH / PDA / PVDF membrane obtained in step (3) was immersed in a cobalt chloride aqueous solution and allowed to stand for 2 hours. The concentration of cobalt chloride was 3.0 mg / mL. Then, an N,N-dimethylformamide solution containing 30 mg / mL of 2,3,6,7,10,11-hexahydroxytriphenyl ligand was added. The volume ratio of the cobalt chloride aqueous solution to the N,N-dimethylformamide solution containing 30 mg / mL of 2,3,6,7,10,11-hexahydroxytriphenyl ligand was 10:1. The membrane was allowed to stand at room temperature for 28 hours. After the reaction was completed, the membrane was rinsed and dried at 60°C to obtain the MOF / LDH / PDA / PVDF composite membrane.

[0045] Example 4 A method for preparing an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation includes the following steps: (1) The hydrophobic polyvinylidene fluoride membrane was placed in a 1.0M sodium hydroxide solution containing 5wt% ethanol and reacted at 65°C for 2 hours. After the reaction was completed, it was rinsed and dried at 50°C to obtain a hydrophilic polyvinylidene fluoride membrane. (2) The hydrophilic polyvinylidene fluoride membrane obtained in step (1) was immersed in Tris-HCl buffer containing dopamine, wherein the concentration of dopamine was 2.0 mg / mL, the concentration of Tris-HCl buffer was 0.1 M, the pH value was 8.5, and the reaction was stirred continuously at room temperature for 7 hours. After the reaction was completed, the membrane was rinsed and dried at 50°C to obtain the PDA / PVDF membrane. (3) Prepare isopropanol solution of cobalt nitrate and aqueous solution of ferrous sulfate respectively. The concentration of metal salt in both solutions is 0.2M. After mixing them at a volume ratio of 3:1, immerse the PDA / PVDF membrane obtained in step (2) into it, stir at room temperature for 26 hours, rinse after the reaction is completed, and dry at 50°C to obtain LDH / PDA / PVDF membrane. (4) The LDH / PDA / PVDF membrane obtained in step (3) was immersed in a cobalt acetate aqueous solution and allowed to stand for 1.5 hours. The concentration of cobalt acetate was 2.0 mg / mL. Then, an N,N-dimethylacetamide solution containing 25 mg / mL of 2,3,6,7,10,11-hexahydroxytriphenyl ligand was added. The volume ratio of the cobalt acetate aqueous solution to the N,N-dimethylacetamide solution containing 25 mg / mL of 2,3,6,7,10,11-hexahydroxytriphenyl ligand was 9:1. The membrane was allowed to stand at room temperature for 26 hours. After the reaction was completed, the membrane was rinsed and dried at 50°C to obtain the MOF / LDH / PDA / PVDF composite membrane.

[0046] Comparative Example 1 Except for omitting steps (3) and (4) in Example 1, the remaining operations are the same as in Example 1, except that the hydrophobic polyvinylidene fluoride membrane is subjected to alkali treatment and dopamine modification in sequence to obtain PDA / PVDF membrane.

[0047] Comparative Example 2 Except for omitting step (4) in Example 1, the remaining operations are the same as in Example 1, that is, the hydrophobic polyvinylidene fluoride membrane is subjected to alkali treatment, dopamine modification and in-situ growth of cobalt iron layered bimetallic hydroxide in sequence to obtain an LDH / PDA / PVDF membrane without a metal-organic framework top layer.

[0048] Application Example 1 The MOF / LDH / PDA / PVDF composite membrane prepared in Example 1 was used to measure the contact angles of the composite membrane with dichloroethane, petroleum ether, toluene, diesel oil, and n-octane underwater. It can be seen that the contact angles of all of these membranes are greater than 150° (e.g., ...). Figure 5 (As shown in a). The roll-off angle between the MOF / LDH / PDA / PVDF composite membrane prepared in Example 1 and dichloroethane was less than 5° in underwater measurements (e.g., as shown in a). Figure 5 (As shown in b) The experimental results show that the MOF / LDH / PDA / PVDF membrane prepared in Example 1 has typical underwater superoleophobic properties and exhibits extremely low adhesion. When an oil-water mixture (such as toluene, dichloroethane, petroleum ether, n-octane, and diesel oil) is poured into a vertically placed glass tube with the composite membrane prepared in Example 1 fixed on it, water passes through while oil is trapped on the membrane material, demonstrating an effective oil-water separation effect.

[0049] Application Example 2 use Figure 6 The experimental setup shown was used to conduct an oil-water mixture separation experiment on the MOF / LDH / PDA / PVDF composite membrane prepared in Example 1. The composite membrane was fixed between two clamps, with an inlet glass tube connected to the top and an outlet glass tube to the bottom. After wetting the membrane material with water, a mixture of diesel oil and water (according to V...) was then... 柴油 / V 水 Prepare 100 mL of oil-water mixture in a ratio of 1:99 (stir thoroughly) and pour it into the upper feed glass tube so that it contacts the membrane. After membrane separation, the water passes through the membrane and flows down from the lower discharge glass tube, while the diesel is blocked above, thus achieving the purpose of separating the oil-water mixture and obtaining separated water and diesel.

[0050] When diesel fuel was replaced with dichloroethane, petroleum ether, toluene, and n-octane, the above experiments were repeated, and similar oil-water separation effects were obtained in all cases.

[0051] Application Example 3 use Figure 6The experimental setup shown was used to perform an oil-water mixture separation experiment on the MOF / LDH / PDA / PVDF composite membrane prepared in Example 2. The composite membrane was fixed between two clamps, with an inlet glass tube connected to the top and an outlet glass tube to the bottom. After wetting the membrane material with water, a mixture of toluene and water (according to V...) was added... 甲苯 / V 水 Prepare 100 mL of oil-water mixture in a ratio of 1:99 (stir thoroughly) and pour it into the upper feed glass tube so that it contacts the membrane. After membrane separation, the water passes through the membrane and flows down from the lower discharge glass tube, while the toluene is blocked above, thus achieving the purpose of separating the oil-water mixture and obtaining separated water and toluene.

[0052] When toluene was replaced with dichloroethane, petroleum ether, diesel oil, and n-octane, the above experiments were repeated, and similar oil-water separation effects were obtained in all cases.

[0053] Application Example 4 use Figure 6 The experimental setup shown was used to conduct an oil-in-water emulsion separation experiment on the MOF / LDH / PDA / PVDF composite membrane prepared in Example 1. The composite membrane was fixed between two clamps, with an inlet glass tube connected to the top and an outlet glass tube to the bottom. After wetting the membrane material with water, an oil-in-water emulsion of petroleum ether and water (according to V...) was introduced. 石油醚 / V 水 Prepare 100.00 mL of oil-water mixture at a ratio of 1:99, then add 50.0 mg of sodium dodecyl sulfate and stir thoroughly to obtain a homogeneous and stable oil-in-water emulsion. Pour the mixture onto the membrane through the upper feed glass tube. The emulsion breaks down as it passes through the membrane, allowing water to pass through and flow down through the lower discharge glass tube, while the oil is blocked at the top. This achieves the separation of the oil-in-water emulsion, yielding the separated water. The separation effect is as follows: Figure 8 As shown. By Figure 8 It can be seen that the emulsion before separation is milky white. Figure 8 In the left bottle of b in the image), a large number of uniformly dispersed oil droplets can be observed under an optical microscope. Figure 8 (a) in the text, while the filtrate after separation is clear and transparent. Figure 8 (The right bottle in b) showed no obvious oil droplets under an optical microscope. Figure 8 c) indicates that the MOF / LDH / PDA / PVDF composite membrane obtained in Example 1 has efficient demulsification and separation capabilities.

[0054] Replacing petroleum ether with any one of dichloroethane, toluene, diesel oil, and n-octane, and repeating the above experiment, similar emulsion separation effects were obtained in all cases.

[0055] Optical microscopy was used to observe and conduct throughput tests on the oil-in-water emulsions before and after separation in this application example. Figure 7In this figure, 'a' represents the separation flux of the MOF / LDH / PDA / PVDF composite membrane prepared in Example 1 for five oil-in-water emulsions: petroleum ether, dichloroethane, toluene, diesel oil, and n-octane, which is 1425.72 L·m⁻¹. -2 ·h -1 3010.69 L·m -2 ·h -1 1200.98 L·m -2 ·h -1 1047.15 L·m -2 ·h -1 2473.72 L·m -2 ·h -1 As can be seen from the figure, the separation efficiency is higher than 99%, indicating that the MOF / LDH / PDA / PVDF composite membrane prepared in Example 1 has excellent separation performance for different types of oil-in-water emulsions. Figure 7 As shown in b, after 10 cycles of separation testing, the MOF / LDH / PDA / PVDF composite membrane prepared in Example 1 showed no significant decrease in separation flux and separation efficiency for petroleum ether / water mixed emulsions, demonstrating good cycle stability and reusability.

[0056] Comparative Test: Under the same conditions as in Application Example 4, the separation of petroleum ether / oil-in-water emulsions was compared by replacing the composite membrane prepared in Example 1 with Comparative Example 1 (PDA / PVDF membrane) and Comparative Example 2 (LDH / PDA / PVDF membrane), respectively. The MOF / LDH / PDA / PVDF composite membrane prepared in Example 1 had an emulsion flux of 1425.72 L·m. -2 ·h -1 The flux recovery rate (FRR) was 96.0%, and the irreversible pollution resistance (R) was... ir The emulsion flux of the PDA / PVDF membrane prepared in Comparative Example 1 was 4.0%. -2 ·h -1 The FRR was 57.5%, R ir The emulsion flux was 42.5%. The LDH / PDA / PVDF membrane prepared in Comparative Example 2 had an emulsion flux of 1943.63 L·m⁻¹. -2 ·h -1 The FRR was 66.3%, R ir The result was 33.7%. From the above comparison results, it can be seen that although the emulsion flux of Example 1 was slightly lower than that of Comparative Examples 1 and 2 (which did not have a metal-organic framework top layer), its FRR was significantly higher than that of the two comparative examples. irThe results were significantly lower than those of the two comparative samples, indicating that although the in-situ constructed metal-organic framework top layer reduced the emulsion flux of the membrane to some extent, it significantly improved the membrane's resistance to irreversible fouling and flux recovery performance after photocatalytic self-cleaning, making a substantial contribution to improving the overall separation performance and antifouling stability of the membrane.

[0057] Application Example 5 use Figure 6 The experimental setup shown was used to perform an oil-in-water emulsion separation experiment on the MOF / LDH / PDA / PVDF composite membrane prepared in Example 2. The composite membrane was fixed between two clamps, with an inlet glass tube connected to the top and an outlet glass tube to the bottom. After wetting the membrane material with water, an oil-in-water emulsion of dichloroethane and water (according to V...) was added... 二氯乙烷 / V 水 Prepare 100.00 mL of oil-water mixture in a ratio of 1:99, then add 50.0 mg of Tween 80 and stir thoroughly to obtain a homogeneous and stable oil-in-water emulsion. Pour the mixture onto the membrane through the upper feed glass tube. The emulsion breaks down as it passes through the membrane, and the water passes through the membrane and flows down from the lower discharge glass tube, while the oil is blocked at the top, thus achieving the purpose of separating the oil-in-water emulsion and obtaining the separated water.

[0058] Replacing dichloroethane with any one of petroleum ether, toluene, diesel oil, and n-octane, and repeating the above experiment, similar emulsion separation effects were obtained in all cases.

[0059] Application Example 6 use Figure 6 The experimental setup shown was used to perform an oil-in-water emulsion separation experiment on the MOF / LDH / PDA / PVDF composite membrane prepared in Example 3. The composite membrane was fixed between two clamps, with the feed glass tube connected to the top and the discharge glass tube to the bottom, respectively. After wetting the membrane material with water, an oil-in-water emulsion of toluene and water (according to V...) was added... 甲苯 / V 水 Prepare 100.00 mL of oil-water mixture in a ratio of 1:99, then add 50.0 mg of Tween 80 and stir thoroughly to obtain a homogeneous and stable oil-in-water emulsion. Pour the mixture onto the membrane through the upper feed glass tube. The emulsion breaks down as it passes through the membrane, and the water passes through the membrane and flows down from the lower discharge glass tube, while the oil is blocked at the top, thus achieving the purpose of separating the oil-in-water emulsion and obtaining the separated water.

[0060] Replacing toluene with any one of petroleum ether, dichloroethane, diesel oil, and n-octane, and repeating the above experiment, similar emulsion separation effects were obtained in all cases.

[0061] Application Example 7 use Figure 6The experimental setup shown was used to perform an oil-in-water emulsion separation experiment on the MOF / LDH / PDA / PVDF composite membrane prepared in Example 4. The composite membrane was fixed between two clamps, with the feed glass tube and discharge glass tube connected to the top and bottom, respectively. After wetting the membrane material with water, an oil-in-water emulsion of n-octane and water (according to V...) was introduced. 正辛烷 / V 水 Prepare 100.00 mL of oil-water mixture in a ratio of 1:99, then add 50.0 mg of sodium dodecyl sulfate and stir thoroughly to obtain a homogeneous and stable oil-in-water emulsion. Pour the mixture onto the membrane through the upper feed glass tube. The emulsion breaks down as it passes through the membrane, and the water passes through the membrane and flows down from the lower discharge glass tube, while the oil is blocked at the top, thus achieving the purpose of separating the oil-in-water emulsion and obtaining the separated water.

[0062] Replacing n-octane with any one of petroleum ether, dichloroethane, diesel oil, and toluene, and repeating the above experiment, similar emulsion separation effects were obtained in all cases.

[0063] The experimental results of this invention show that the MOF / LDH / PDA / PVDF composite membrane material obtained by the method of this invention has advantages such as fast separation speed and good separation effect. It is suitable for the separation and treatment of general oil-water mixtures and oil-water emulsions, and can separate oil-water mixtures and mixed oil-water emulsions containing oils such as dichloroethane, petroleum ether, toluene, diesel, and n-octane. Moreover, the MOF / LDH / PDA / PVDF composite membrane material has extremely low adhesion properties, can be reused repeatedly, and has a stable oil-water separation effect.

[0064] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. An in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation, characterized in that, It consists of a polymer base film and a polydopamine layer, a layered double metal hydroxide layer and a metal-organic framework layer sequentially constructed in situ on its surface; The polymer base membrane is a hydrophilic polyvinylidene fluoride membrane; The layered bimetallic hydroxide is a cobalt-iron layered bimetallic hydroxide; The metal-organic framework is formed by cobalt ions coordinated with 2,3,6,7,10,11-hexahydroxytriphenyl ligands.

2. The in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation according to claim 1, characterized in that, The polydopamine layer is formed by the self-polymerization of dopamine under alkaline conditions.

3. The in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation according to claim 1, characterized in that, The hydrophilic polyvinylidene fluoride membrane is obtained by treating a hydrophobic polyvinylidene fluoride membrane with an alkali.

4. A method for preparing an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation as described in any one of claims 1 to 3, characterized in that, Includes the following steps: (1) The hydrophobic polyvinylidene fluoride membrane was placed in an alkaline solution and reacted under heating conditions. After the reaction was completed, it was washed and dried to obtain a hydrophilic polyvinylidene fluoride membrane. (2) The hydrophilic polyvinylidene fluoride membrane obtained in step (1) is immersed in Tris-HCl buffer containing dopamine and stirred continuously at room temperature. After the reaction is completed, it is washed and dried to obtain a PDA / PVDF membrane. (3) Prepare organic solvent solutions of cobalt salt and aqueous solutions of ferrous salt respectively. After mixing the two solutions, immerse the PDA / PVDF membrane obtained in step (2) into them and stir the reaction at room temperature. After the reaction is completed, wash and dry to obtain LDH / PDA / PVDF membrane. (4) Immerse the LDH / PDA / PVDF membrane obtained in step (3) in a cobalt salt aqueous solution and let it stand. Then add an organic solvent solution containing 2,3,6,7,10,11-hexahydroxytriphenyl ligands and let it stand at room temperature for reaction. After the reaction is completed, wash and dry to obtain the MOF / LDH / PDA / PVDF composite membrane.

5. The preparation method according to claim 4, characterized in that, The alkaline solution mentioned in step (1) is a 0.8-1.2M sodium hydroxide solution containing 3-7 wt% ethanol; The reaction temperature under the heating conditions is 50~70℃, and the reaction time is 1~3 hours.

6. The preparation method according to claim 4, characterized in that, The concentration of dopamine mentioned in step (2) is 1.5~2.5 mg / mL; The concentration of the Tris-HCl buffer solution is 0.08~0.12M, and the pH value is 8.0~9.0; The continuous stirring reaction lasts for 4 to 8 hours.

7. The preparation method according to claim 4, characterized in that, The cobalt salt mentioned in step (3) is at least one of cobalt nitrate, cobalt chloride, and cobalt acetate; The ferrous salt is at least one of ferrous sulfate, ferrous chloride and ferrous nitrate; The solvent in the organic solvent solution of the cobalt salt is at least one of isopropanol, ethanol and methanol; The volume ratio of the organic solvent solution of the cobalt salt to the aqueous solution of the ferrous salt is 2:1 to 4:1, and the concentration of the metal salt in both solutions is 0.1 to 0.3 M. The stirring reaction at room temperature is carried out for 20 to 28 hours.

8. The preparation method according to claim 4, characterized in that, The cobalt salt mentioned in step (4) is at least one of cobalt nitrate, cobalt chloride and cobalt acetate, and the concentration of the cobalt salt in its aqueous solution is 1~3 mg / mL; In the organic solvent solution containing 2,3,6,7,10,11-hexahydroxytriphenyl ligands, the solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide and ethylene glycol, and the concentration of the ligand is 20~30 mg / mL; The volume ratio of the cobalt salt aqueous solution to the organic solvent solution containing 2,3,6,7,10,11-hexahydroxytriphenyl ligand is 8:1 to 10:

1. The settling time is 0.5 to 2 hours; The time for the reaction to stand at room temperature is 20 to 28 hours.

9. The application of an in-situ constructed MOF / LDH / PDA / PVDF composite membrane material for oil-water emulsion separation as described in any one of claims 1 to 3 in oil-water separation.

10. The application according to claim 9, characterized in that, The oil-water separation is oil-water mixture separation and / or oil-water emulsion separation; The oil in the oil-water mixture separation is selected from at least one of the following: toluene, dichloroethane, petroleum ether, n-octane, and diesel oil; The oil-water emulsion separation refers to the separation of oil-water emulsions without surfactants or oil-water emulsions containing surfactants.